2007
DOI: 10.1152/ajpregu.00569.2007
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary run training but not estradiol deficiency alters the tibial bone-soleus muscle functional relationship in mice

Abstract: The study's objective was to investigate how estrogen deficiency and run training affect the tibial bone-soleus muscle functional relationship in mice. Female mice were assigned into one of two surgical conditions, ovariectomy (OVX) or sham ovariectomy (sham), and one of two activity conditions, voluntary wheel running (Run) or sedentary (Sed). To determine whether differences observed between OVX and sham conditions could be attributed to estradiol (E(2)), additional OVX mice were supplemented with E(2). Tibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 40 publications
1
38
0
Order By: Relevance
“…We chose to assess the hindlimb dorsiflexor EDL muscle ex vivo for contractility and susceptibility to injury for consistency between this and our previous work (29). Mice were anesthetized with pentobarbital sodium (25 mg/kg BM) and muscles were mounted to a dual-mode muscle lever system (300B-LR; Aurora Scientific) and incubated at 25°C in an oxygenated bath as previously described (1,6,36). Muscles were maintained at a 0.4 g resting tension (Lo) throughout the experiment (as per 34,35).…”
Section: Methodsmentioning
confidence: 99%
“…We chose to assess the hindlimb dorsiflexor EDL muscle ex vivo for contractility and susceptibility to injury for consistency between this and our previous work (29). Mice were anesthetized with pentobarbital sodium (25 mg/kg BM) and muscles were mounted to a dual-mode muscle lever system (300B-LR; Aurora Scientific) and incubated at 25°C in an oxygenated bath as previously described (1,6,36). Muscles were maintained at a 0.4 g resting tension (Lo) throughout the experiment (as per 34,35).…”
Section: Methodsmentioning
confidence: 99%
“…The second theory predicts that the increase in muscle strength is protective; that is, muscle acts as a shock absorber to lessen cortical bending and strain during running. With the animal model, Warren et al (14) found that short-term training induced an increase in the strength of muscle relative to bone; however, this did not increase the bone's susceptibility to fracture in direct bending tests of ultimate strength. They concluded that the longer the muscle-to-bone functional capacity mismatch continued to exist, the greater would be the chance for occurrence of a stress fracture.…”
Section: Etiology Of Stress Fracturementioning
confidence: 99%
“…It should be noted that all muscle and bone measurements were made before the 12-wk training program. It would be of interest to evaluate changes in muscle and bone during such a training program to see whether the muscle-bone strength imbalance increases, as would be predicted from the study by Warren et al (14).…”
Section: Etiology Of Stress Fracturementioning
confidence: 99%
See 2 more Smart Citations